Demand and socio economic aspects of up market condominium dwellers in Kuala Lumpur - Abu Zarin, Hasmah; Bujang, Ahmad Ariffian; Ismail, Maziah (1996)
In recent years, condominium living has gained popularity among Malaysians. Many Malaysian have invested in this development because of its product atributes. It has become the mode of living for the coutry's middle and upper class families. Condominium developments have mushroomed in all parts of cities in Malaysia particularly in Kuala Lumpur. The residence can enjoy the convinience of having the facilities at their doorsteps, the abundance of greenary and open space. Demand for up-market condominium in Kuala Lumpur is not certain and so this is a main problem to the developers. The developers are in doubt about which factor and how much weight should be considered to come up with the condominium project. What are the real factors that influence the demand or what are the real factors that attract people to buy the condominiums? Besides this factors, who are the target groups because each ethnic group have different type of demand. Once this factors are known, it is easier for the developers to consider these factors before they proceed with the condominium development effectively and efficiently.